Optimization of M4 positive allosteric modulators (PAMs): The discovery of VU0476406, a non-human primate in vivo tool compound for translational pharmacology. Issue 11 (1st June 2017) - Melancon, Bruce J.; Wood, Michael R.; Noetzel, Meredith J.; Nance, Kellie D.; Engelberg, Eileen M.; Han, Changho; Lamsal, Atin; Chang, Sichen; Cho, Hyekyung P.; Byers, Frank W.; Bubser, Michael; Jones, Carrie K.; et al.
Graphical abstract: Abstract: This letter describes the further chemical optimization of the 5-amino-thieno[2, 3- c ]pyridazine series (VU0467154/VU0467485) of M4 positive allosteric modulators (PAMs), developed via iterative parallel synthesis, culminating in the discovery of the non-human primate (NHP) in vivo tool compound, VU0476406 (8p ). VU0476406 is an important in vivo tool compound to enable translation of pharmacodynamics from rodent to NHP, and while data related to a Parkinson's disease model has been reported with8p, this is the first disclosure of the optimization and discovery of VU0476406, as well as detailed pharmacology and DMPK properties.